Exponential stability analysis and l1 synthesis of positive T-S fuzzy systems with time-varying delays. (May 2017) - Meng, Min; Lam, James; Feng, Jun-e; Zhao, Xudong; Chen, Xiaoming
Abstract: The α -exponential stability analysis and l 1 controller synthesis of positive Takagi–Sugeno fuzzy discrete-time systems with time-varying delays are discussed in this paper. A sufficient condition of α -exponential stability for autonomous positive fuzzy systems is first established by constructing a new Lyapunov–Krasovskii functional, which depends on a given scalar 0 < α < 1 and the bound of time-varying delays. Then, a sufficient condition for controlled systems with l 1 gain constraint is also presented while imposing α -exponential stability, upon which, a constrained l 1 controller is designed for both single-input and multi-input cases. Finally, an example is given to show the feasibility of the theoretical results.